The Relationship Between Work Posture and the Risk of Carpal Tunnel Syndrome in Openwork Craftsmen in the Village Mongolian - Nurzihan Adam; Rona Febriyona; Andi Nur Aina Sudirman (PROMOTOR, 2024)
Work posture is the posture of the body at the time of work. Different work attitudes will produce different strengths. When working, postures are designed to occur naturally, thereby reducing musculoskeletal injuries. The purpose of this study was to determine the relationship between work posture and the risk of carpal tunnel syndrome in openwork craftsmen in Mongolato Village, the type of research is quantitative with a cross-sectional approach, a population of 84 openwork craftsmen in Mongolato Village, a sample of 45 openwork craftsmen, which was determined by purposive sampling techniques, the statistical test used was Chi-Square, The research instrument is a questionnaire. The results showed that the work posture of the craftsmen could trigger the risk of carpal tunnel syndrome events and the results of chi-square analysis obtained p-value = 0.007>0.05. Based on the results of the analysis of 45 filigree craftsmen, it is known that craftsmen who have a work posture in the medium risk category totaled 27 respondents, with 20 respondents experiencing moderate carpal tunnel syndrome and 7 respondents experiencing high carpal tunnel syndrome. For craftsmen who have a high-risk work posture, there are 18 respondents, namely 6  respondents with moderate carpal tunnel syndrome and 12 respondents with high carpal tunnel syndrome. This study concludes that there is a relationship between work posture and the risk of carpal tunnel syndrome in filigree craftsmen. Advice for craftsmen to pay more attention to good work posture for work so that they can avoid the risk of carpal tunnel syndrome.